PENGEMBANGAN MULTIMEDIA INTERAKTIF IPA UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Anik Sundari; Hendri Marhadi; Tuti Purwoningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low learning motivation and students' critical thinking skills are still major problems in the learning process, especially in learning dominated by conventional methods and minimal use of digital media. This study aims to develop interactive multimedia that is valid, practical, and effective in improving students' learning motivation and critical thinking skills. This study uses the Research and Development (R & D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects of this study were 31 fifth-grade students of Sepat 3 Masaran Elementary School. Data collection techniques used learning motivation questionnaires, expert validation sheets, student response questionnaires, teacher response questionnaires, and critical thinking ability tests. Research data were analyzed using descriptive statistics and the N-Gain Test. The results of the study showed that the interactive multimedia developed was in the feasible category based on the results of the validation test by media experts and material experts, each obtaining an average score percentage of 80.00% and 78.33%, as well as the small group trial student response questionnaire with an average score percentage of 80.00% and a large group trial student response questionnaire with an average score percentage of 79.50%. In addition, the results of the effectiveness test showed a significant increase in students' learning motivation and critical thinking skills after using interactive multimedia compared to before the intervention. Students' learning motivation increased from previously obtaining an average score percentage of 38.71% to 79.03% after using interactive multimedia products. Meanwhile, students' critical thinking skills were in the moderate category with an N-gain value of 0.67. These findings indicate that interactive multimedia is able to create more interesting, contextual learning and encourage students' active involvement in higher-order thinking processes. Thus, the developed interactive multimedia has the potential to be an effective alternative learning media to support improving the quality of learning and developing 21st-century competencies.